Model development and comparison of different heuristics for production planning in large volume softwood sawmills. Issue 11 (2nd November 2017) - Huka, Maria Anna; Gronalt, Manfred
ABSTRACT: This study investigates the production planning at softwood sawmills dealing with the co-production of several products. The problem is formulated as a mixed-integer program and applied to a real-size case study. For comparison purposes, five different heuristics are used for comparison with optimization in different settings and for which the loss in performance is investigated. A sensitivity analysis is performed for the initial parameters of storage values of products and raw materials. In addition, the importance of parameters like variable costs, available raw materials, and minimal cutting quantity is investigated. Furthermore, several different planning time horizons are compared for varying periods. In general, it can be concluded that the real-life inspired heuristics are worse than the optimization results and more sensitive to the parameters. When applying the multi-period model in a rolling planning horizon, the best heuristic outperforms it owing to the end effects included in the model.